La Ética y la Función Pública - Acosta, Nelly; Ojeda La Serna, Vivian; Mina Páez, Alexandra (Revista Ecos de la Academia, 2021)
Abstract Ethics in the public function determines different areas in which the State and public servants face the uncertainty of knowing how to act based on the legitimacy of the facts. In this ethical aspect, it is necessary to act out of conviction supported by laws and norms that govern the actions of the public employee, convinced that applying a law or norm is beneficial for both the public servant and the State. This research aims to analyze the current state of ethics in the public function and how it has been oriented towards the creation of a Code of Ethics to regulate situations presented in the public sphere. From a bibliographic approach, credit is given to the research of other authors through documentary review, thus bringing together the most important studies on ethics and public function. As a result, it is highlighted that these issues have been dealt with for decades, despite the existence of codes, ways are sought to violate the laws and justify wrong human acts. Therefore, ethical participation in the development of the processes of the State and public servants has not been achieved. Keywords: Ethics, Public Function, State, Code of Ethics